The Relationship between the Length of Seeking Help and the Severity of Stroke Patients - Prayitno, Untung; Kristiyawati, Sri Puguh; Yono, Novi Heri (Universitas Aisyiyah Yogyakarta, 2023)
The length of time a stroke patient seeks help from health services plays an important role in the successful treatment of stroke patients. The golden period for stroke treatment is approximately only 3 hours from the start of the attack. Once an attack occurs, the patient must receive comprehensive therapy so that the degree of nerve damage is not severe. The aim of the research was to determine the relationship between the length of time seeking help and the severity of stroke patients at RSUD dr. Loekmono Hadi Kudus. This research is descriptive analytical with a cross-sectional approach. The research sample was taken using a purposive sampling technique. A sample of 65 respondents was obtained. The instruments used were observation sheets and the NIHSS questionnaire, while statistical tests used Spearman Rank. There is a significant relationship between the length of time seeking help and the severity of stroke patients (p-value <0.05). More than half of the respondents sought help from health services after the golden period (>3 hours), and more than half of the respondents experienced a serious stroke. Respondents' or families' ignorance of the signs and symptoms of stroke, as well as consideration of treatment costs, are the dominant factors in patients missing their golden years. Therefore, educating the public about stroke, especially the signs and symptoms of stroke, is very important so that the public can immediately take patients to the hospital. Future researchers are expected to conduct qualitative research to explore knowledge and responses to stroke attacks.